Aktualisasi Komisi Kepolisian Nasional Dalam Mewujudkan Reformasi Kepolisian Negara Republik Indonesia - Yusuf, Yusuf; Harmoko, Harmoko (JUSTISI, 2024)
This research examines the actualization of Kompolnas in realizing Polri reform. This research attempts to look at the actualization of Kompolnas and the challenges faced by Kompolnas in carrying out police reform. The approach used in this research is normative law. The legal materials used in this research are primary and secondary legal materials. Legal materials were collected systematically through library research and documentation, then the legal materials were analyzed systematically using deductive and inductive legal reasoning, with the results of the analysis described in this study. The results of this study reveal that Kompolnas' efforts in implementing Polri reform have not been maximized because they do not have the legal authority to evaluate the results of their recommendations. Besides that, there are still obstacles faced by Kompolnas in realizing Polri reform, namely internal factors and external factors. Keywords: Actualization, Kompolnas, Reform, Polri